Chapter 14 Template Tuning and Graded Consciousness - Brogaard, Berit (Taylor & Francis, 2024)
Whether visual perceptual consciousness is gradable or dichotomous has been the subject of fierce debate in recent years. If perceptual consciousness is gradable, perceivers may have less than full access to-and thus be less than fully phenomenally aware of-perceptual information that is represented in working memory. This raises the question of in virtue of what a subject can be less than fully perceptually conscious. In this chapter, we provide an answer to this question, according to which inexact categorizations of visual input may result in a representation of the visual information in working memory that is less than fully available to the perceiver and which the perceiver therefore is less than fully phenomenally aware of. The latter proposal is a natural extension of a theory of perception we have proposed in previous works, viz., the template tuning theory (TTT). We argue that TTT is compatible with both gradable and dichotomous conceptions of perceptual consciousness but that the available empirical evidence favours a gradable conception of perceptual consciousness.